ショウワ キチ フキン ニ オケル カイスイ オンド エンチョク ブンプ ノ 1984 ネン 9 ツキ カラ 1985 ネン 1 ツキ ニ カケテ ノ ヘンドウ - 松田, 治; マツダ, オサム; 石川, 慎吾; イシカワ, シンゴ; 川口, 弘一; カワグチ, コウイチ; 西澤, 廣紀; ニシザワ, ヒロキ; Matsuda, Osamu; Ishikawa, Shingo; Kawaguchi, Kouichi; Nishizawa, Hiroki (1990)
P(論文) 第25次南極地域観測隊の海洋生物環境調査の一環として, 昭和基地付近の定着氷上の一定点において海氷温度の鉛直分布を観測した。観測は1984年9月より1985年1月まで毎月1回実施し, この間の氷厚は139cmから155cmであった。海氷内の温度は表層(5cm部位)と最下層でそれぞれ-15.2～-0.3℃, -2.0～-0.3℃の間で変化し, 鉛直的には深度に対しほぼ直線的な変化を示した。最低温度は9月から1月にかけて次第に上昇した。 Observation on the vertical distribution of the sea ice temperature was carried out at a station near Syowa Station. During the monthly observation from September 1984 to January 1985,the thickness of ice varied between 139cm and 155cm. Since the bottom ice temperature resembled the underlying seawater temperature, while the surface ice approached the air temperature, distribution of temperature generally showed a steep gradient across ice. The sea ice temperature at the surface and the bottom varied from -15.2 to -0.3℃ and from -2.0 to -0.3℃, decreasing with depth. The minimum temperature of sea ice rose from September to January. departmental bulletin paper